Identifying and Assessing the Development of Populations of Undocumented Migrants: The Case of Undocumented Poles and Bulgarians in Brussels - Mila Paspalanova (Fondazione Eni Enrico Mattei (FEEM), 2006)
The stocks of undocumented migrants residing on the territory of Europe and the continuous flows of clandestine migrants are currently one of the hottest social and political topics. Even though the issue of irregular migration is on the top of many political and academic agendas the knowledge about who the undocumented migrants are, how they can be identified and how their population in a country develops numerically, remains limited. In this context, the aim of the current paper is twofold. In the first place, snowball sampling will be introduced as a technique for identifying undocumented migrants on the territory of a country and in the second, the empirical results from sampling and assessing the stability of the populations of undocumented Poles and Bulgarians in Brussels will be presented.
Keywords: C89; 330; Snowball Sampling; Undocumented Migrants